Tinjauan Epistemologi Terhadap Pancasila Sebagai Dasar Negara Republik Indonesia - Surajiyo, Surajiyo (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
Pancasila was not born as an epistemological system. Pancasila was born as the basis ofthe State, is an ideology and contains a view of life. This happened in 1945. Epistemology wasborn long before the birth of Pancasila. Epistemology was born from the efforts of the sophists inAncient Greece to modern times, which placed the study of epistemology as closely related to thestructure of knowledge.The epistemological basis of Pancasila is essentially inseparable from is ontological basis.Pancasila as an ideology is rooted in its basic values, namely the philosophy of Pancasila.Therefore, the basic epistemology of Pancasila cannot be separated from its basic concept ofhuman nature. If humans are the ontological basis of Pancasila, then it has implications for theepistemological building, namely the epistemological building placed in the building of humanphilosophy. The research was carried out in a literal way, with a literature review of selected booksand journals or scientific magazines containing descriptions of philosophy, ideology, Pancasilaphilosophy, epistemology, philosophy of science, and history of philosophy. The data needed isqualitative data that is processed by the reflective method, equipped with the 'verstehen' method.The issue of epistemology in relation to Pancasila is intended to find sources ofknowledge, the truth of Pancasila and the composition of Pancasila as a system of knowledge. Thesource of knowledge from Pancasila is seen from the flow of knowledge, namely empiricism andrationalism.